The Future of Criminal Law within the European Union - Union Law or Community Law Competence? - Murshetz, Verena (Victoria University of Wellington Law Review, 2007)
Recent developments regarding criminal matters within the European Union (EU) show a trend towards a supranational criminal competence, which could be realised before the entry into force of the European Constitution whose future is uncertain. The strongest indicators in this development are two judgments of the European Court of Justice (ECJ), one that extends the powers of the European Community (EC) over the protection of the environment through criminal sanctions and the other applying the principle of conforming interpretation to framework decisions . This trend is questionable though, as the Treaty of the European Union (TEU) does not confer a criminal competence upon the EC. The third pillar containing criminal matters is intergovernmental in nature. This article critically discusses the recent trend and presents arguments against an implied supranational criminal law within the EU.